Local country food sources of methylmercury, selenium and omega-3 fatty acids in Nunavik, Northern Quebec - Lemire, Mélanie; Kwan, Michael K.H.; Anassour-Laouan Sidi, Elhadji; Ayotte, Pierre; Muckle, Gina; Dewailly, Éric; Pirkle, Catherine (Science of The Total Environment, 2019)
Country foods are central to Inuit culture and replete in selenium (Se) and long-chain omega-3 polyunsaturated fatty acids (n-3 PUFA). However, some marine country foods bioaccumulate high concentrations of methylmercury (MeHg). Se and n-3 are associated with several health benefits in Nunavik, Northern Quebec, but, recent studies show that prenatal MeHg exposure is associated with visual, cognitive and behavioral deficit later in childhood. The study objectives are to identify contemporary country food sources of MeHg, Se and long-chain n-3 PUFA in Nunavik, particularly among childbearing-age women, taking into account regional differences in consumption profiles. The contribution of different country foods to daily MeHg, Se, long-chain n-3 PUFA intake (μg/kg body weight/day) was estimated using: (i) country food consumption and blood biomarkers data from the 2004 Nunavik Health Survey (387 women, 315 men), and (ii) data on MeHg, Se, long-chain n-3 PUFA concentrations found in Nunavik wildlife species. In the region where most traditional beluga hunting takes place in Nunavik, the prevalence of at-risk blood Hg (≥ 8 μg/L) in childbearing-age women was 78.4%. While most country foods presently consumed contain low MeHg, beluga meat, not a staple of the Inuit diet, is the most important contributor to MeHg: up to two-thirds of MeHg intake in the beluga-hunting region (0.66 of MeHg intake) and to about one-third in other regions. In contrast, seal liver and beluga mattaaq - beluga skin and blubber - only mildly contributed to MeHg (between 0.06 and 0.15 of MeHg intake), depending on the region. Beluga mattaaq also highly contributed to Se intake (0.30 of Se intake). Arctic char, beluga blubber and mattaaq, and seal blubber contributed to most long-chain n-3 PUFA intake. This study highlights the importance of considering interconnections between local ecosystems and dietary habits to develop recommendations and interventions promoting country foods' benefits, while minimizing the risk of MeHg from beluga meat, ...